Feed selectivity of laying hens undergoing different beak trimming in two rearing systems Seletividade alimentar de galinhas poedeiras submetidas a diferentes métodos de debicagem em dois sistemas de criação - Baggio R.A.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.The present research was conducted to evaluate whether different beak trimming methods and rearing systems affected the feed selectivity of laying hens. A total of 178 Hy-line Brown laying hens in the growing phase and 120 hens in the production phase were divided in a factorial arrangement (2 x 3), with two rearing systems (floor and cages) and three beak trimming methods: without beak trimming (control), hot-blade beak trimming, and infrared beak trimming, with four replicates. Laying hens were feed with isonutritive diets. Samples were collected from feed orts and feed provided, with a subsequent analysis of dry matter, crude energy, crude protein, mineral matter, geometric mean diameter and geometric standard deviation. The results were subjected to the error normality test, analysis of variance and the Fisher-Snedecor (P<0.05) and Duncan tests (P<0.05). The beak trimming methods evaluated were not sufficient to prevent feed selection in laying hens. However, in the growing phase, hot-blade beak trimming reduced feed selection capacity of laying hens more than did infrared beak trimming. The cage system favored feed selection, both in the growing and production phases.